Exploring on the Use of Kaonak Greeting as Non-Verbal Communication by the Papuan Native in Jayapura City - Aulia, Tegar; Sahib, Rahmawansyah; Wijayanti, Erfin; Ita Rahmawati, Suci (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study aims to investigate the function of kaonak greetings as non-verbal communication of native Papuans and the implementation of kaonak greetings by native Papuans in Jayapura city. This research used qualitative method design, where data is collected through observation and interview. The data sources of this study are native Papuan in Jayapura city. This study uses Miles and Huberman technique of analysis those are data reduction, data display and conclusion. Based on the results of the study, there are five functions of the kaonak greeting. Namely as a symbol of familiarity, as a symbol of respect for elders, as a symbol of peace, as a symbol of cultural identity and as a symbol of the non-Papuan approach to native Papuans. In addition, the results of this study also explain how the implementation of kaonak greetings by native Papuans in everyday life. In its implementation, kaonak greetings are not much different from greetings in general which are carried out when meeting or want to separate, and kaonak greetings are also often used to make an agreement, and when apologized. However, the findings of this study provide recommendations for Indonesian people visiting Papua. An information and guide in building stronger communication and emotional relationships between communities in Papua, especially the Amber community towards the Komin community.